Learning Autodesk Maya 8. - Guindon, Marc-André; McGinnis, Cathy (Autodesk/Sybex, 2006)
Learning autodesk maya 8 Foundation is your key to unlocking the power of autodesk maya software, directly from the creators of one of the world's most powerful 3D animation and effects software products. Get hands-on experience with the innovative tools and powerful techniques available in maya 8 through all new project-based lessons.